2005
DOI: 10.1158/1078-0432.ccr-05-1152
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2C8, CYP3A4, CYP3A5, and ABCB1 Polymorphisms with the Pharmacokinetics of Paclitaxel

Abstract: Purpose: To retrospectively evaluate the effects of six known allelic variants in the CYP2C8, CYP3A4, CYP3A5, and ABCB1 genes on the pharmacokinetics of the anticancer agent paclitaxel (Taxol). Experimental Design: A cohort of 97 Caucasian patients with cancer (median age, 57 years) received paclitaxel as an i.v. infusion (dose range, 80-225 mg/m 2 ). Genomic DNA was analyzed using PCR RFLP or using Pyrosequencing. Pharmacokinetic variables for unbound paclitaxel were estimated using nonlinear mixed effect mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
4
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 57 publications
8
116
4
2
Order By: Relevance
“…42 To our knowledge, this is the largest prospective study reporting this association. The results, however, are in somewhat contrast to Henningsson et al 43 who found no correlation between clearance and CYP2C8*3, CYP2C8*4 and ABCB1 C3435T in 97 patients (male and female) treated with paclitaxel (80-225 mg m -2 ) and Marsh et al 44 who found no correlation between clearance and CYP2C8*3, CYP2C8*4, ABCB1 C1236T and ABCB1 G2677T in 93 patients with breast cancer treated with 24-h paclitaxel infusion (575-775 mg m -2 ). This discrepancy can be explained by chance or: in case of the study by Henningsson et al, by gender in so far that Joerger et al 45 showed a 20% higher elimination of paclitaxel in males than in females, and in the case of the study by Marsh et al 46 by the nonlinear elimination of paclitaxel reported in the studied population.…”
Section: Discussioncontrasting
confidence: 91%
“…42 To our knowledge, this is the largest prospective study reporting this association. The results, however, are in somewhat contrast to Henningsson et al 43 who found no correlation between clearance and CYP2C8*3, CYP2C8*4 and ABCB1 C3435T in 97 patients (male and female) treated with paclitaxel (80-225 mg m -2 ) and Marsh et al 44 who found no correlation between clearance and CYP2C8*3, CYP2C8*4, ABCB1 C1236T and ABCB1 G2677T in 93 patients with breast cancer treated with 24-h paclitaxel infusion (575-775 mg m -2 ). This discrepancy can be explained by chance or: in case of the study by Henningsson et al, by gender in so far that Joerger et al 45 showed a 20% higher elimination of paclitaxel in males than in females, and in the case of the study by Marsh et al 46 by the nonlinear elimination of paclitaxel reported in the studied population.…”
Section: Discussioncontrasting
confidence: 91%
“…34 One recent study in ovarian cancer identified an association between ABCB1 2677G4A/T and response to paclitaxel in 53 Swedish ovarian cancer patients, 35 but this could not be replicated in a larger ovarian cancer study, 36 and was not seen in the breast cancer patients in this study. Although in vitro evidence suggests a role for CYP2C8 and CYP3A4 in paclitaxel metabolism, 4,5 it is possible that other variables such as epigenetic regulation mask these effects in vivo.…”
Section: Resultscontrasting
confidence: 58%
“…This question has been dealt with by Nakajima et al (2005), who found a 16-fold interindividual variation in the 6a-hydroxypaclitaxel area under the curve (AUC) among 23 female ovarian cancer patients, but apparently no CYP2C8 variant alleles, due to the small study or low frequency of the alleles in Japanese. Recently, Henningsson et al (2005), using 97 patients, found a 13-fold variation in paclitaxel clearance but no significant influence of the CYP2C8*2, CYP2C8*3 and CYP2C8*4 variant alleles. This issue, however, warrants further investigations.…”
Section: Cyp2csmentioning
confidence: 98%